Effectiveness of second step program in fostering social-emotional skills in young children: a study in Japan - Rikuya Hosokawa; Riho Tomozawa; Megumi Fujimoto (BMC Pediatrics)
Abstract Background Interest in social-emotional skills in the context of school maladjustment is growing, and social-emotional learning can help develop such skills. Second Step is a social-emotional skills approach prevalent in several countries. In Asian countries, including Japan, preventive interventions for school maladjustment in young children are scarce, and their effectiveness is not adequately validated. This study examines the effectiveness of the social-emotional learning “Second Step program” among children aged 4 to 5 years. Methods In 2022, the Second Step program was implemented on a class-by-class basis for children aged 4 to 5 years enrolled in middle grades of a kindergarten in Japan. The program included 25 sessions, each lasting one hour on average, approximately once a week. To test the effectiveness of the program, kindergarten teachers assessed the children’s social skills. Parents assessed their children’s behaviors. Data of 73 children in the intervention group and 91 in the control group were analyzed. The intervention group participated in the Second Step program, while the control group did not participate in any program. Evaluations were conducted before and after the intervention program. Results Children in the intervention group displayed significantly greater assertiveness, self-control, and cooperation scores following program implementation compared with those in the control group. They also showed significantly lower scores on behavioral problems compared with those in the control group and before the program. The intervention had a meaningful impact on both social competencies and behavioral outcomes. Specifically, the effect sizes for social competencies in the intervention group were moderate to large, reflecting substantial improvements. Conclusions The social-emotional learning Second Step program implemented on a classroom basis may be effective in early childhood. An early approach targeting kindergarten-aged children is necessary to prevent school maladjustment.